DETERMINAN YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN PUBLIK DI INDONESIA - wibowo, Devina Kesya; Murni, Yetty; Damayanti, Ameilia (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
The purpose of this research is to determine the effect of green accounting, total asset turnover and corporate social responsibility on company profitability. This research uses secondary data seen through financial reports based on the Indonesia Stock Exchange website. The population used is coal subsector mining companies for the 2019-2023 period, where there are 18 companies that meet the standard criteria for conducting research. The testing in this research uses multiple linear regression method and uses SPSS version 26. The results of this research show that green accounting has no effect on profitability, total asset turnover has an effect on profitability, and corporate social responsibility has an effect on profitability.